The simplicity of cider - Reichert, Amy E., 1974- (Gallery Books, 2017)
"Fall in love with The Simplicity of Cider, the charming new novel about a prickly but gifted cider-maker whose quiet life is interrupted by the arrival of a handsome man and his young son at her family's careworn orchard by the author of The Coincidence of Coconut Cake and Luck, Love & Lemon Pie. Focused and unassuming fifth generation cider-maker Sanna Lund has one desire: to live a simple, quiet life on her family's apple orchard in Door County, Wisconsin. Although her business is struggling, Sanna remains fiercely devoted to the orchard, despite her brother's attempts to convince their aging father to sell the land. Single dad Isaac Banks has spent years trying to shield his son Sebastian from his troubled mother. Fleeing heartbreak at home, Isaac packed up their lives and the two headed out on an adventure, driving across the country. Chance--or fate--led them straight to Sanna's orchard. Isaac's helping hands are much appreciated at the apple farm, even more when Sanna's father is injured in an accident. As Sanna's formerly simple life becomes increasingly complicated, she finds solace in unexpected places--friendship with young Sebastian and something more deliciously complex with Isaac--until an outside threat infiltrates the farm. From the warm and funny Amy E. Reichert, The Simplicity of Cider is a charming love story with a touch of magic, perfect for fans of Sarah Addison Allen and Gayle Forman"--